2005
DOI: 10.1080/08927020500065801
|View full text |Cite
|
Sign up to set email alerts
|

Grid computing and molecular simulations: the vision of theeMinerals project

Abstract: This paper discusses a number of aspects of using grid computing methods in support of molecular simulations, with examples drawn from the eMinerals project. A number of components for a useful grid infrastructure are discussed, including the integration of compute and data grids, automatic metadata capture from simulation studies, interoperability of data between simulation codes, management of data and data accessibility, management of jobs and workflow, and tools to support collaboration. Use of a grid infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This, of itself, means there is a need for new approaches to job and data management in simulation studies and this paper considers these issues in detail. Grid computing requires new ways of running and managing simulation studies and the work reported in this paper is taken from experience gained by the UK eMinerals project [1] in developing grid computing methods for molecular simulations. The focus of the discussion will be a case study of the compressibility anomaly in amorphous silica using molecular dynamics simulations with the new DL_POLY_3 code [2,3] suitably adapted for the needs of grid computing.…”
Section: Introductionmentioning
confidence: 99%
“…This, of itself, means there is a need for new approaches to job and data management in simulation studies and this paper considers these issues in detail. Grid computing requires new ways of running and managing simulation studies and the work reported in this paper is taken from experience gained by the UK eMinerals project [1] in developing grid computing methods for molecular simulations. The focus of the discussion will be a case study of the compressibility anomaly in amorphous silica using molecular dynamics simulations with the new DL_POLY_3 code [2,3] suitably adapted for the needs of grid computing.…”
Section: Introductionmentioning
confidence: 99%
“…(i) The researcher uploads the data files and executables to the data grid. In the case of the eMinerals project (Dove & de Leeuw 2005) this has been the Storage Resource Broker (SRB; Baru et al 1998), although RMCS is not constrained to work only with the SRB. (ii) The researcher uses the rmcs_submit command with a job description file as the argument.…”
Section: Rmcs Architecture and Usementioning
confidence: 99%
“…As discussed in the introduction to this collection of papers [1], the eMinerals project is a collaboration between molecular simulation scientists, molecular simulation code developers and computing specialists, with participation from a number of different departments (Earth Sciences, Computer Science and Chemistry) and UK institutes (Universities of Cambridge, Reading and Bath, University College London, Birkbeck College, the Royal Institution, and the Daresbury Laboratory). The broad aim of the project is to develop a cross-institute infrastructure to support the molecular simulation scientists using grid technologies [2].…”
Section: Introductionmentioning
confidence: 99%